Failure of Administrative Data to Guide Asthma Care - Joel Agarwal; Jennifer LaBranche; Jessica Cohen; Chris de Gara; Dilini Vethanayagam (Spectrum, 2018)
Rationale: Asthma is a chronic inflammatory disease of the airways that is very common (7.9% of Canadians over the age of 12). Despite numerous clinical guidelines, education events and administrative data reviews, there has been little change to the way asthma is managed in the Canadian health care system for nearly 30 years. We evaluated, through the Physician Learning Program (PLP) in Alberta, possible reasons why administrative datasets have not been able to provide meaningful information to adjust health policy.